2014
DOI: 10.1039/c3cp54364a
|View full text |Cite
|
Sign up to set email alerts
|

Polarization control of metal-enhanced fluorescence in hybrid assemblies of photosynthetic complexes and gold nanorods

Abstract: a Fluorescence imaging of hybrid nanostructures composed of a bacterial light-harvesting complex LH2and Au nanorods with controlled coupling strength is employed to study the spectral dependence of the plasmon-induced fluorescence enhancement. Perfect matching of the plasmon resonances in the nanorods with the absorption bands of the LH2 complexes facilitates a direct comparison of the enhancement factors for longitudinal and transverse plasmon frequencies of the nanorods. We find that the fluorescence enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…By tuning the spacing between the molecules and metallic substrate, coupling effect between SPR and excited state molecules can be moderated [84]. Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90].…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…By tuning the spacing between the molecules and metallic substrate, coupling effect between SPR and excited state molecules can be moderated [84]. Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90].…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…The former is challenging for our set-up to collect sufficient signal and the latter would be highly technically challenging requiring super-resolution detection of native chromophores (rather than idealized fluorophores designed for super-resolution applications). We have shown proof-of-concept for the utility of nanoscale topography and optical detection of low-number of complexes for observing NPQ switching, we suggest that extending this combinatorial approach to also incorporate metal nanoparticles for localized enhancement of excitation or emission [ 70 ] could allow the ultimate in vitro platform for mapping how NPQ changes and exciton dynamics change within native-like membrane environments with single-protein optical and topographic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the interactions of gold or silver NPs with photosynthetic proteins have focussed in the main on the photophysical consequences, including enhanced absorption and energy transfer. [80][81][82][83][84][85][86][87][88][89][90][91][92] A smaller number of studies have reported the impact of plasmonic interactions on photocurrents from photosynthetic materials on electrodes or in cells. Enhancements have been seen after placing Photosystem I complexes on a silver island film 93 and decorating thylakoid membranes with gold nanorods.…”
Section: Discussionmentioning
confidence: 99%